Comparison of Declarative-Interrogative Intonation in Lampungnese - Redika Cindra Reranta (Universitas Teknokrat Indonesia, 2021)
Intonation is a suprasegmental feature of language that constructs the meaning of utterances. The meaning constructed can be different from the lexical meaning and syntactical structure. This paper tried to examine the intonation system in the Lampung language, especially the acoustic characteristics which distinguish between declarative and interrogative. In this research, the researcher applied the IPO approach to collect and analyze data. Data were gathered by recording native speakers uttering declarative and interrogative sentences that were segmentally identical. Having the data, a perception test was conducted to get the best utterances for each mode as a contour prototype. Next, both prototypes were analyzed respectively using Praat software to find out each acoustic characteristic. Then, they were compared to find the suprasegmental features that characterize the acoustic features of each sentence mode. Based on the analysis, both intonations differed in the pitch of initial, final subject constituent, final complement constituent, initial predicate constituent, final pitch, peak, range of pitch, and duration of utterances. In addition, pitch of peak (H1) and slope (H2) were identified as the most influential component in the formation of a sentence model. Therefore, experiments of manipulating those acoustic features (H1 and H2) and testing them on the perception of native speakers were held to prove the identification. The result of the perception test showed that the peak significantly distinguished the mode of the sentence, the higher pitch of the peak determined the interrogative mode. While the second identification did not give any contribution in creating the meaning.